Future Patient Demand for Shoulder Arthroplasty by Younger Patients: National Projections. Issue 6 (June 2015) - Padegimas, Eric M.; Maltenfort, Mitchell; Lazarus, Mark D.; Ramsey, Matthew L.; Williams, Gerald R.; Namdari, Surena
Abstract: Background: The outcomes of shoulder arthroplasties in younger patients (55 years or younger) are not as reliable compared with those of the general population. Greater risk of revision and higher complication rates in younger patients present direct costs to the healthcare system and indirect costs to the patient in terms of quality of life. Previous studies have suggested an increased demand for shoulder arthroplasties overall, but to our knowledge, the demand in younger patients has not been explored. Questions/purposes: We asked: (1) What was the demand for shoulder arthroplasties between 2002 and 2011 in the United States for all patients and a specific subpopulation of patients who were 55 years old or younger? (2) How is the demand for shoulder arthroplasties in younger patients projected to change through 2030? (3) How is procedural demand projected to change in younger patients through 2030, and specifically, what can we anticipate in terms of hemiarthroplasty volume compared with that of total shoulder arthroplasty? Methods: We used the National Inpatient Sample database to identify primary shoulder arthroplasties performed between 2002 and 2011. A Poisson regression model was developed using the National Inpatient Sample data and United States Census Bureau projections on future population changes to predict estimated national demand for total shoulder arthroplasties and hemiarthroplasties in all patients and in the subpopulation 55 years old or younger. This model was projected until 2030, with associated 95% CIs. We then specifically analyzed the projected demand of hemiarthroplasties and compared this with demand for all arthroplasty procedures in the younger patient population. Results: Demand for shoulder arthroplasties in patients 55 years or younger is increasing at a rate of 8.2% per year (95% CI, 7.06%‐9.35%), compared with a growth rate of 12.1% (95% CI, 8.35%‐16.02%) per year for patients older than 55 years. In 2002, 15.9% (3587 of 22, 617 captured in the National Inpatient Sample) of primary shoulder arthroplasties were performed in patients 55 years old or younger. In 2011, the relative size of the younger patient population had decreased to 11.0% (7001 of 63, 784) of all recipients of shoulder arthroplasties. The demand for primary shoulder arthroplasties among younger patients is projected to increase by 333.3% (95% CI, 257.0%‐432.5%) from 2011 to 2030. However, in patients older than 55 years demand is projected to increase by 755.4% (95% CI, 380.7%‐1511.1%). Therefore, despite the increased predicted demand for shoulder arthroplasties in younger patients, they are predicted to account for only 4% of all recipients by 2030. The rate of hemiarthroplasties in patients 55 years or younger showed a 16.5% decline per year (95% CI, 16.1%‐17.1%) from 2002 (53.6% of all arthroplasties) to 2011 (34.2% of all arthroplasties). By 2030, hemiarthroplasties are projected to account for only 23.5% of all shoulder arthroplasties in patients 55 years or younger. Conclusions: The demand for shoulder arthroplasties in younger patients continues to increase in the United States; however, rates of hemiarthroplasties are declining. The demand has substantial implications for future revision arthroplasties, which include the direct healthcare costs of revision arthroplasty, the indirect societal burden of missed productivity owing to time away from work, and the increased burden of the need for qualified surgeons to meet the demand. Despite the increasing rate of arthroplasties performed in younger patients, current and projected demands remain greater for older patients, indicating a disproportionately greater need for shoulder arthroplasties in older patients. This is in contrast to the trends observed in the literature regarding hip and knee arthroplasties that show projected demands to be greater in younger patients. Factors responsible for the difference in demand require further investigation but may be related to changing indications, reported poorer outcomes in younger patients, the increased popularity of reverse shoulder arthroplasties in the elderly, or the evolution of nonarthroplasty options. Level of Evidence: Level III, prognostic study.